As tramas de um diálogo: relações intersubjetivas nas entrevistas de Clarice Lispector - Rossi, Vera Helena Saad (2011)
The main object of this research is the journalistic production of Clarice Lispector over the years of 1950-1970, a time when she actively collaborated with major carioca newspapers. This is an important part of the writer s work, which we know better now, thanks to the work of the researcher Aparecida Maria Nunes. Assuming, hypothetically, that the journalist reveals the writer, we seek to establish relations between the Clarice Lispector journalistic and literary writing. The corpus is made up of 83 interviews conducted by the writer for the magazine Manchete in the section Possible Dialogues with Clarice Lispector, where we have 59 interviews between May 1968 and outubro1969, and the magazine Fatos e Fotos/Gente, where we have 24 interviews conducted between December 1976 and October 1977. We analyze the warp of the dialogue during the interviews under the concept of Freudian unheimlich (uncanny) and "dialogism"of Bakhtin. We have also studied the "newjournalism" and "nonfiction novel" genres, whose main representative was Truman Capote, author of In Cold Blood, who argued that non-fiction could be as artistic and compelling as fiction. Methodologically the research is bibliographic and documentary: on one hand, we make the state of the art of critical reception of Clarice, on the other, we study the material relating to journalistic collaborations